Effects of dietary zinc level and ractopamine HCl on pork chop tenderness and shelf-life characteristics - Paulk, Chad B.; Tokach, Michael D.; Nelssen, Jim L.; Burnett, Derris D.; Vaughn, Mathew A.; Phelps, Kelsey J.; Dritz, Steven S.; DeRouchey, Joel M.; Goodband, Robert D.; Houser, Terry A.; Haydon, K. D.; Gonzalez, John M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 320 finishing pigs (PIC 327 × 1050; initially 216 lb) were utilized to determine the effects of adding Zn to diets containing ractopamine HCl (RAC) on muscle fiber type distribution, fresh chop color, and cooked meat characteristics. Dietary treatments were fed for approximately 35 d and consisted of: a corn-soybean meal–based negative control (CON); a positive control diet with 10 ppm of RAC (RAC+); and the RAC+ diet plus 75, 150, or 225 ppm added Zn from either ZnO or Availa-Zn. Loins from 80 barrow and 80 gilt carcasses were evaluated. No Zn source effect or Zn source × level interactions we observed during the study (P > 0.10). Pigs fed the RAC+ had increased (P < 0.02) percentage type IIX and a tendency for increased percentage type IIB muscle fibers. Increasing added Zn decreased (linear, P = 0.01) percentage type IIA and tended to increase (P = 0.09) IIX muscle fibers. On d 1, 2, 3, 4, and 5 of display, pork chops from pigs fed the RAC+ treatment had greater (P < 0.03) L* values (lighter) compared with the CON. On d 0 and 3 of display, increasing added Zn tended to decrease (quadratic, P = 0.10) L* values and decreased (quadratic, P < 0.03) L* values on d 1, 2, 4, and 5. Pigs fed RAC+ had decreased (P < 0.05) a* values (less red) on d 1 and 4 of display and tended to have decreased (P < 0.10) a* values on d 0 and 2 compared with CON pork chops. RAC+ decreased (P < 0.001) metmyoglobin reducing ability (MRA) of pork chops on d 5. Chops from pigs fed added Zn had increased (quadratic, P < 0.03) MRA on d 3 and 5 of the display period. There was a trend for increased (linear, P = 0.07) cooking loss as added Zn increased in RAC diets. In conclusion, RAC+ diets produced chops that were lighter and less red but maintained a higher percentage of surface oxymyoglobin throughout a 5-d simulated retail display. RAC+ reduced MRA at the end of the display period, but supplementing Zn to RAC diets restored MRA to near CON treatment levels at the end of the display period.
Keywords: Ractopamine HCL; Pork color; Pork quality; Fiber type; Pork chop shelf life